Phases I-II Matched Case-Control Study of Human Fetal Liver Cell Transplantation for Treatment of Chronic Liver Disease. Issue 8 (August 2015) - Pietrosi, Giada; Vizzini, Giovanni; Gerlach, Jorg; Chinnici, Cinzia; Luca, Angelo; Amico, Giandomenico; D'amato, Monica; Conaldi, Pier Giulio; Petri, Sergio Li; Spada, Marco; Tuzzolino, Fabio; Alio, Luigi; et al.
Fetal hepatocytes have a high regenerative capacity. The aim of the study was to assess treatment safety and clinical efficacy of human fetal liver cell transplantation through splenic artery infusion. Patients with endstage chronic liver disease on the waiting list for liver transplantation were enrolled. A retrospectively selected contemporary matched-pair group served as control. Nonsorted raw fetal liver cell preparations were isolated from therapeutically aborted fetuses. The end points of the study were safety and improvement of the Model for End-Stage Liver Disease (MELD) and Child-Pugh scores. Nine patients received a total of 13 intrasplenic infusions and were compared with 16 patients on standard therapy. There were no side effects related to the infusion procedure. At the end of follow-up, the MELD score (mean ± SD) in the treatment group remained stable from baseline (16.0 ± 2.9) to the last observation (15.7 ± 3.8), while it increased in the control group from 15.3 ± 2.5 to 19 ± 5.7 ( p = 0.0437). The Child-Pugh score (mean ± SD) dropped from 10.1 ± 1.5 to 9.1 ± 1.4 in the treatment group and increased from 10.0 ± 1.2 to 11.1 ± 1.6 in the control group ( p = 0.0076). All treated patients with history of recurrent portosystemic encephalopathy (PSE) had no further episodes during 1-year follow-up. No improvement was observed in the control group patients with PSE at study inclusion. Treatment was considered a failure in six of the nine patients (three deaths not liver related, one liver transplant, two MELD score increases) compared with 14 of the 16 patients in the control group (six deaths, five of which were caused by liver failure, four liver transplants, and four MELD score increases). Intrasplenic fetal liver cell infusion is a safe and well-tolerated procedure in patients with end-stage chronic liver disease. A positive effect on clinical scores and on encephalopathy emerged from this preliminary study.